Analysis of Product Quality Control Using FTA (Fault Tree Analysis) Method - Gladies Putri Suprapto; Dwi Sukma Donoriyanto (Yayasan Riset dan Pengembangan Intelektual, 2024)
Shoes are one of the protectors of the human body as footwear used for daily activities. In addition to being a means of body protection, shoes are currently used as school uniforms. CV. Esa Kalen Jaya is a company that produces upper school shoes. But CV Essay Kalen Jaya experienced problems in the production, namely uncontrolled defective products produced by 1,542 pairs of upper shoes. So the need for analysis of the causes of defects and provide suggestions for quality improvement due to factors that cause product defects. To be able to determine the root cause of product defects used FTA (fault tree analysis) method.The result is that the cause of the occurrence of disability is caused by 9 factors. With improvement recommendations conduct training and evaluation on a regular basis to help improve the ability of workers in sewing so as to minimize errors.